Innovation in the High-Tech Economy - Chuan, Pang.; Khachidze, Vasil; Lai, Ivan K.W.; Liu, Yide.; Siddiqui, Sohail; Wang, Tim.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the First International Conference on Management Science and Engineering: Innovation and High-tech Services, ICMSE 2013, held in Macau, in June 2013. The papers are contributed by innovative researchers, engineers and practitioners in the field of management science, information system, finance, economics and accounting and offer a platform for exchanging the latest research findings in the field of management science and management innovation, for looking forward to the future trends in the management science and management innovation field in the 21st century, and to promote management modernization and high-tech innovation services.
Development Strategy of E-health in China -- E-commerce of Eco Bags on Basis of Pareto Improvement -- The Impact of Technical Barriers to Trade: The Cases of Trade between China, Japan, Korea, and the US -- An Appraisal of Internet Business Models as a Research Paradigm -- The Study of Usability Performance in the E-Commerce Websites -- E-Business and Cloud Computing: A New Practice or a Trend -- Multi-Level Access Control in the Data Pipeline of the International Supply Chain System -- A  Smart Parking and Reservation System for QR-Code-Based Car Park -- A Study on Smart Work Center -- An OGS-based Dynamic Time Warping Algorithm for Time Series Data -- Analysis of Operators’ Smart Home Products Industry Chain Cooperation Model Based on Game Theory Perspective -- Examining Factors Correlated with Consumer Online Shopping Behaviour -- Effects of Social Needs, Social Influences and Convenience on Smartphones Dependency.
Keywords: Management; Industrial management; Finance; Innovation/Technology Management; Finance, general